Isolated Colonic Histoplasmosis in Patients Undergoing Immunomodulator Therapy: A Systematic Review - Faisal Inayat MBBS; Gul Nawaz MD; Arslan Afzal MD; Maleeha Ajmal MD; Marjan Haider MD; Muhammad Sarfraz MD; Zaka Ul Haq MD; Sobaan Taj MD; Rizwan Ishtiaq MD (SAGE Publishing, 2023)
Gastrointestinal histoplasmosis remains an inconspicuous clinicopathologic entity. It is predominantly considered a protean manifestation of disseminated disease. We hereby delineate a unique case of biopsy-proven isolated colonic histoplasmosis in a patient undergoing methotrexate therapy. Furthermore, we present the first systematic review of the MEDLINE, Google Scholar, Embase, and Scopus databases regarding isolated colonic histoplasmosis in adult patients receiving immunomodulator therapy (IMT). A total of 13 case reports (level of clinical evidence: IV) were identified. The mean age was 55.6 ± 11.1 years, with 9 (69.2%) cases reported in women. Patients with subclinical disease (5, 38.5%) were often incidentally diagnosed by screening colonoscopy. Symptomatic individuals predominantly presented with diarrhea (4, 30.8%), weight loss (3, 23.1%), and/or abdominal pain (3, 23.1%). IMT was mainly administered for liver transplant (4, 30.8%), renal transplant (4, 30.8%), and ulcerative colitis (2, 15.4%). Common colonoscopy features included colonic ulcerations (7, 53.8%), polyps or pseudopolyps (3, 23.1%), and/or mass-like lesions (3, 23.1%). Diagnosis was made by histology of colonic biopsy in 11 (84.6%) and resected specimens in 2 (15.4%) patients. Treatment consisted of a combination of amphotericin B with oral itraconazole in 6 (46.2%), oral itraconazole alone in 5 (38.5%), and amphotericin B alone in 2 (15.4%) patients. Complete clinical recovery was achieved in all patients. This article illustrates that isolated colonic involvement can be the only clinical presentation of histoplasmosis. It may masquerade as other bowel disorders, presenting diagnostic and therapeutic conundrums. Gastroenterologists should rule out colonic histoplasmosis in IMT recipients who develop unexplained colitis symptoms.